Solar PV Microgrids Implementation model: A case study of Local Self Governments in the Indian State of Kerala - Ajith, Gopi; K., Sudhakar; Ngui, Wai Keng (IOP Publishing, 2021)
The State of Kerala in Southern part of India has significant potential for generation of power from renewable energy sources, especially solar energy. Most of the PV projects in the State are being implemented on roof-tops due to the unavailability of land area in the densely populated State for large utility scale PV power plants. The concept of implementing Solar PV projects by empowering Local Self Governments has been explained in this paper by illustrating the case study of the Indian State of Kerala. The respective Local Self Governments like Municipal Corporations are playing a key role in Kerala in this decision-making process to accomplish model carbon free solar communities by installing Solar Photovoltaic Projects. The requirement of local beneficiary will be analysed by local trained experts and feasibility study will be conducted for the beneficiary communities involving residential buildings, local industries and commercial institutions and educational institutions and the PV projects will be implemented utilising the local E.P.C players. Local Self Governments like Municipal Corporations were empowered to plan, formulate and implement their own Solar Photovoltaic Projects. This approach is being implemented in Kerala resulting in solar electrification of local communities/institutions through the decentralised approach. This created a new business model at the local level involving trained manpower and supply chain for meeting the Local Self Government targets for new PV projects in order to achieve the targets of carbon free communities.